Fatores de risco para as condições pós-covid: um estudo de caso controle - La Scaléa, Ana Cristina Ribeiro (Universidade Federal de São Carlos, 2025)
This study aimed to analyze the risk factors of users of the Unified Health System for the development of Post-Covid Conditions (PCC). It is an unmatched case-control study conducted at the University Hospital of the Federal University of São Carlos, the Epidemiological Surveillance Service, and the Basic and Outpatient Care Department of São Carlos municipality. The study sample consisted of 821 PCC cases and 821 controls who received a laboratory confirmed diagnosis of Covid-19 between March 2020 and December 2023. Data were collected, entered into an Excel spreadsheet, and analyzed using descriptive statistics and logistic regression to calculate crude and adjusted Odds Ratios (OR), adopting a 5% significance level. The results showed that individuals aged 18–29 and 30–39 had a lower likelihood of developing PCC compared to older age groups (40–79 years). Women were 55% more likely to develop PCC than men. There was no association between race/ethnicity, comorbidities, and PCC. Non-hospitalized individuals were 11.6 times more likely to develop PCC compared to those hospitalized, and unvaccinated individuals were at higher risk of PCC than vaccinated individuals (OR ranging from 4.9 to 9.0 depending on vaccination status). The five most prevalent PCC symptoms identified were fatigue (17.1%), headache (16.6%), shortness of breath (13.5%), cough (12.4%), and lower limb pain (11.5%). In the analysis of risk factors for headache, individuals aged 18–29 were 2.2 times more likely to experience headache as a PCC symptom compared to those aged 40–49. Regarding shortness of breath, individuals without comorbidities were 55% less likely to report this symptom, and unvaccinated individuals were 2.7 times more likely to develop shortness of breath than vaccinated individuals. For cough, individuals aged 18–29 were 4 times more likely to experience this symptom compared to those aged 70 or older. Regarding lower limb pain, individuals aged 18–29 were 69% less likely to report this symptom compared to those aged 30–39, and individuals who did not require hospitalization during acute Covid-19 were 49% less likely to report lower limb pain than those who were hospitalized. Therefore, the prevalence of PCC symptoms is associated with age, sex, comorbidities, and vaccination status. Given the ongoing presence of Covid-19, it is essential to strengthen vaccination campaigns against the acute disease and train healthcare professionals to support individuals with PCC.
Risk factors for post-covid conditions: a case-control study
Keywords: Covid-19; Condições pós-covid; Fatores de risco; Post-covid conditions; Risk factors; CIENCIAS DA SAUDE::ENFERMAGEM